2023
DOI: 10.1029/2022je007607
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Turbulence at Jezero Crater as Determined From MEDA Measurements and Modeling

Abstract: Mars 2020 Mars Environmental Dynamics Analyzer (MEDA) instrument data acquired during half of a Martian year (Ls 13°–180°), and modeling efforts with the Mars Regional Atmospheric Modeling System (MRAMS) and the Mars Climate Database (MCD) enable the study of the seasonal evolution and variability of nocturnal atmospheric turbulence at Jezero crater. Nighttime conditions in Mars's Planetary Boundary Layer are highly stable because of strong radiative cooling that efficiently inhibits convection. However, MEDA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Nighttime pressure drops can be driven by orographic mechanical turbulence at Gale crater (Ordonez‐Etxeberria et al., 2018), and by the interaction of a low‐level jet and weak stability in Elysium (Chatain et al., 2021). In Jezero, nighttime turbulence appears in different atmospheric fields (winds, pressure and temperature) and has the characteristics of a bore‐like disturbance (Pla‐Garcia et al., 2022) that could be the cause of the nighttime pressure drops not associated to the heat island effect.…”
Section: Pressure Drops: Vortices Dust Devils Convective Cells and Wavesmentioning
confidence: 99%
“…Nighttime pressure drops can be driven by orographic mechanical turbulence at Gale crater (Ordonez‐Etxeberria et al., 2018), and by the interaction of a low‐level jet and weak stability in Elysium (Chatain et al., 2021). In Jezero, nighttime turbulence appears in different atmospheric fields (winds, pressure and temperature) and has the characteristics of a bore‐like disturbance (Pla‐Garcia et al., 2022) that could be the cause of the nighttime pressure drops not associated to the heat island effect.…”
Section: Pressure Drops: Vortices Dust Devils Convective Cells and Wavesmentioning
confidence: 99%
“…De la Torre Juárez et al ( 2023) further analyzed the statistical properties of fluctuations of MEDA winds and temperatures on selected sols to find different turbulence regimes in the near surface atmosphere, and Munguira et al (2023) quantified the thermal oscillations over 400 sols as a proxy of the varying level of daytime near-surface convective activity at Jezero, finding a linear relation between temperature fluctuations and thermal gradients during daytime. An additional analysis by Pla-García et al (2023) concluded that topographic flows driving turbulence during nighttime also cause temperature fluctuations.…”
Section: Temperature Fluctuations and Atmospheric Stability As A Func...mentioning
confidence: 99%